2019
DOI: 10.1371/journal.pone.0217864
|View full text |Cite
|
Sign up to set email alerts
|

Early warning systems in obstetrics: A systematic literature review

Abstract: Introduction Several versions of Early Warning Systems (EWS) are used in obstetrics to detect and treat early clinical deterioration to avert morbidity and mortality. EWS can potentially be useful to improve the quality of care and reduce the risk of maternal mortality in resource-limited settings. We conducted a systematic literature review of published obstetric early warning systems, define their predictive accuracy for morbidity and mortality, and their effectiveness in triggering corrective a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 28 publications
2
68
3
1
Order By: Relevance
“…There was no change in the proportion of obstetric complications, ICU admission and length of hospital stay following EWS implementation. Obstetric EWS have been previously shown to prevent progressive obstetric morbidity (Shields et al, 2016;Hedriana et al, 2016;Umar A., et al, 2019). In contrast to our findings also, Shields and colleagues, in a large multicentre quasi-experimental trial, reported a significant reduction in severe and composite maternal morbidity (p<0.01) as defined by the Centre for Disease Control (CDC), but not mortality, in six intervention hospitals following EWS implementation, compared to 19 controls (Shields et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was no change in the proportion of obstetric complications, ICU admission and length of hospital stay following EWS implementation. Obstetric EWS have been previously shown to prevent progressive obstetric morbidity (Shields et al, 2016;Hedriana et al, 2016;Umar A., et al, 2019). In contrast to our findings also, Shields and colleagues, in a large multicentre quasi-experimental trial, reported a significant reduction in severe and composite maternal morbidity (p<0.01) as defined by the Centre for Disease Control (CDC), but not mortality, in six intervention hospitals following EWS implementation, compared to 19 controls (Shields et al, 2016).…”
Section: Discussioncontrasting
confidence: 99%
“…Obstetric EWS is recommended for monitoring the condition of hospitalised pregnant and postnatal women, based on predetermined abnormal values (warning signs) to generate a rapid medical response and facilitate early detection and management of clinical deterioration (ACOG, 2013;CEMACH, 2007;Edwards et al, 2015;Mhyre et al, 2014;Shields, 2016). A recent systematic review of EWS used in obstetrics reported that they are effective in predicting adverse obstetric outcomes and reducing obstetric morbidity (Umar A. et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the implementation of the Obstetric EWS has been found to be effective in predicting severe morbidity, to contribute to improved quality of care, to prevent progressive obstetric morbidity and to improve health outcomes [21]. However, there is limited evidence of the effectiveness of the Obstetric EWS in reducing maternal death across all settings [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Obstetric EWS tool has been found to be effective in predicting severe morbidity (in general obstetric population) and mortality (in critically ill obstetric patients) (Umar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the implementation of the Obstetric EWS has been found to contribute to improved quality of care, prevent progressive obstetric morbidity and improve health outcomes (Umar et al, 2019). However, there is limited evidence of the effectiveness of the Obstetric EWS in reducing maternal death across all settings (Umar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%